Motivation of Female Engineers in the Construction Industry in Bosnia and Herzegovina - Hodzic, E.; El Sayed, A.; Novalic, A. (Engineering, Technology & Applied Science Research, 2022)
Abstract-Female engineers go through different stages during their professional careers due to natural life processes and factors. In developing countries, it is not rare for managers to avoid hiring female engineers, due to these factors and the conservative belief that construction is a male-dominated industry. In Bosnia and Herzegovina (B&H) there are a few studies that refer to the motivation in the construction industry, but none that refer to the position of women in the construction industry and their motivation based on the selected demographic factors. This study aims to fill this research gap, utilizing quantitative research methods. The sample included female engineers of different profiles, working in the construction industry, who were required to fulfill the Multidimensional Work Motivation Scale (MWMS). The five considered demographic factors are age, family status, number of children, education level, and professional experience. The results of this research showed that family status does not affect any motivation dimension, whereas professional experience affects all motivation dimensions except the identified regulations. External–material regulations consist the most influential motivation dimension for female engineers in the construction industry in B&H, whereas amotivation, and introjected regulations were the least. It is recommended for managers and human resources to use the findings of this research in order to keep the female construction engineers motivated and satisfied in their workplace or to know what motivation dimensions to use during the hiring process.